Aluminum alloy material with low thermal conductivity and preparation method thereof
By adding specific MAX phase materials to aluminum alloy materials and adopting ball milling and hot press sintering processes, the problem of insufficient thermal conductivity of aluminum alloy materials is solved, and a low thermal conductivity and low cost aluminum alloy material preparation is achieved, which meets near-zero energy Efficiency requirements for exterior windows for building use.
Patent Information
- Application Number
- CN202310143154.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-21
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-02-21
AI Technical Summary
The existing aluminum alloy materials lack thermal conductivity in the exterior windows for building near zero energy consumption and have high production costs, which affects the energy efficiency and economics of the building.
Aluminum alloy material with low thermal conductivity was prepared by adding tin titanium carbide and aluminum titanium carbide MAX phase material, combined with ball milling and hot press sintering processes.
It significantly reduces the thermal conductivity of aluminum alloy materials, improves the thermal insulation performance of buildings, meets the requirements of nearly zero energy consumption for building exterior windows, and reduces production costs.
Smart Images

Figure BDA0004088223280000081 
Figure BDA0004088223280000082
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal materials, and in particular to an aluminum alloy material with low thermal conductivity and a preparation method thereof. Background Art
[0002] The development of near-zero energy building exterior windows is still in its infancy in my country, and there are very few companies that can develop and design such products. At present, the main technical means of aluminum alloy near-zero energy building exterior windows are to increase the width of the insulation strip and the number of cavities, and fill low thermal conductivity materials in the larger cavity of the insulation strip, and configure low-radiation coated glass. The total number of glass layers is more than three layers, and the glass cavity is filled with inert gas and equipped with warm edge spacers; the appearance design is mostly a design where the outdoor side frame and sash are flush, while the indoor side frame and sash are not flush; the drainage design uses open drainage and additional drainage hole cover decoration; fixed screens are used to prevent mosquitoes and flies. The disadvantages of such a structure are also obvious: 1. Although a variety of insulation measures have been adopted, the thermal insulation effect is still not ideal; 2. The drain hole cover is exposed, which is prone to whistling sounds and easy to fall off in windy weather, affecting the appearance; 3. The outside of the window frame is equipped with fixed screens or no screens. Residents cannot maintain and clean the fixed screens by themselves and must seek professional help; 4. The frame and fan on the indoor and outdoor sides are not on the same plane, affecting the appearance.
[0003] The patent application document with publication number CN104674069A discloses a low thermal conductivity, high performance and energy-saving aluminum alloy, which is made of the following components in parts by weight: 85-95 parts of aluminum, 2-4 parts of silicon carbide, 1-3 parts of iron, 0.2-1 parts of copper, 0.2-1 parts of manganese, 0.8-1.2 parts of magnesium, 0.1-0.3 parts of calcium, 1-3 parts of titanium carbide, 1-3 parts of calcined kaolin, 2-4 parts of additives, 0.2-1 parts of silicotungstic acid, and 0.2-1 parts of nano-ceramic powder; the additives are made of the following components in parts by weight: 5 parts of graphene microsheets, 5 parts of boron nitride, 5 parts of gypsum, 3 parts of potassium titanate whiskers, 5 parts of slaked lime powder, 0.5 parts of talc, 2 parts of rare earth, 0.5 parts of tungsten carbide, and 2 parts of aluminum borate whiskers. The aluminum alloy adds low thermal conductivity materials such as kaolin, silicotungstic acid, additives, and nano-ceramic powder to the formula to reduce the thermal conductivity of the aluminum alloy, but simultaneously adds graphene microsheets. The graphene microsheets maintain the original planar carbon hexagonal conjugated crystal structure of graphite and have excellent electrical and thermal conductivity. The graphene microsheets significantly improve the thermal conductivity of the aluminum alloy. At the same time, the cost of the graphene microsheets is relatively high, which increases the production cost of the aluminum alloy.
[0004] The patent application document with publication number CN 110592442A discloses a low thermal conductivity and high toughness aluminum-manganese-cobalt series die-cast aluminum alloy, whose components include Mn: 1-1.5%, Co: 0.1-0.9%, Mg: 7-9%, Cr: 0.1-0.3%, Ni: 0.1-0.2%, Si: 1.5-2.5%, trace elements: 0-0.5%, impurity elements ≤ 0.5%, and the balance is Al. The alloy not only has the advantage of low thermal conductivity, but also has good strength to meet market demand. However, the thermal conductivity coefficient of the die-cast aluminum alloy is about 80, and the heat conduction effect is obvious, which still cannot meet the requirements of the exterior windows of near-zero energy consumption buildings.
[0005] Based on the above situation, the present invention proposes an aluminum alloy material with low thermal conductivity and a preparation method thereof. Summary of the invention
[0006] The object of the present invention is to provide an aluminum alloy material with low thermal conductivity and a preparation method thereof.
[0007] To achieve the above-mentioned purpose, the present invention provides an aluminum alloy material with low thermal conductivity, which is prepared from the following raw materials in percentage by mass: Mn: 0.5-1.0wt%, Co: 0.1-0.4wt%, Mg: 2-4wt%, Cr: 0.1-0.2wt%, Ni: 0.1-0.2wt%, 0.5-1.0wt% of tin-titanium carbide MAX phase material, impurities not exceeding 0.1wt%, and the balance being aluminum.
[0008] Preferably, the source of the aluminum is aluminum powder, and the sources of manganese, magnesium, chromium, cobalt and nickel are intermediate alloys containing aluminum.
[0009] Preferably, the titanium tin carbide MAX phase material includes one or a combination of two or more of a 312 phase titanium tin carbide MAX phase material, a 211 phase titanium tin carbide MAX phase material, and a 413 phase titanium tin carbide MAX phase material.
[0010] Preferably, the tin titanium carbide MAX phase material is a 211 phase tin titanium carbide MAX phase material, and the 211 phase tin titanium carbide MAX phase material is Ti 2 SnC.
[0011] Preferably, the aluminum alloy material further comprises 2.0-3.0 wt % of aluminum-titanium carbide MAX phase material.
[0012] Preferably, the aluminum titanium carbide MAX phase material includes one or a combination of two or more of a 312 phase aluminum titanium carbide MAX phase material, a 211 phase aluminum titanium carbide MAX phase material, and a 413 phase aluminum titanium carbide MAX phase material.
[0013] Preferably, the aluminum titanium carbide MAX phase material is a 312 phase aluminum titanium carbide MAX phase material, and the 312 phase aluminum titanium carbide MAX phase material is Ti 3 AlC 2 .
[0014] The aluminum alloy material is prepared from the following raw materials in percentage by mass: Mn: 0.5-1.0wt%, Co: 0.1-0.4wt%, Mg: 2-4wt%, Cr: 0.1-0.2wt%, Ni: 0.1-0.2wt%, 0.5-1.0wt% of tin-titanium carbide MAX phase material, 2.0-3.0wt% of aluminum-titanium carbide MAX phase material, no more than 0.1wt% of impurities, and the balance is aluminum.
[0015] Preferably, the aluminum alloy material is prepared from the following raw materials in the following mass percentages: Mn: 1.0wt%, Co: 0.4wt%, Mg: 4wt%, Cr: 0.2wt%, Ni: 0.2wt%, 1.0wt% of tin titanium carbide MAX phase material, 3.0wt% of aluminum titanium carbide MAX phase material, no more than 0.1wt% of impurities, and the balance is aluminum.
[0016] The present invention also provides a method for preparing an aluminum alloy material with low thermal conductivity, the preparation method comprising the following steps:
[0017] (1) placing aluminum titanium carbide MAX phase material and aluminum powder in a ball mill, placing a steel ball with a diameter of 6 to 8 mm at a ball-to-material ratio of 10:1, evacuating and filling with argon gas with a purity of ≥99.0%, and then ball milling at a speed of 400 to 500 r / min for 10 to 12 hours, then adding tin titanium carbide MAX phase material, and continuing to ball mill at a speed of 400 to 500 r / min for 10 to 12 hours to obtain a mixed powder containing MAX phase material;
[0018] (2) placing an aluminum-manganese master alloy in a ball mill, adding steel balls with a diameter of 8 to 10 mm at a ball-to-material ratio of 15:1, and ball milling at a speed of 400 to 500 r / min for 5 to 6 hours, and then adding an aluminum-cobalt master alloy, an aluminum-chromium master alloy, an aluminum-magnesium master alloy, and an aluminum-nickel master alloy in order, the former master alloy being ball milled before the latter master alloy is added, and when the latter master alloy is added, steel balls are added at a ball-to-material ratio of 15:1 to obtain a master alloy powder;
[0019] (3) The mixed powder containing the MAX phase material obtained in step (1) and the master alloy powder obtained in step (2) are stirred and mixed at 500-600 rpm for 20-25 min, then poured into a hot pressing sintering mold cavity coated with boron nitride, and cold pressed at a pressure of 100-200 MPa for 1-2 h;
[0020] (4) In an atmosphere of argon gas with a purity of ≥99.0%, the temperature is raised to 980-990°C at a heating rate of 10°C / min, kept at that temperature for 120-140min and then furnace cooled, wherein pressurization is started when the temperature is raised to 700-750°C, and the pressure is increased to 50-60MPa when the temperature reaches 900°C, and then the pressure is maintained until the furnace is cooled.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention can further reduce the thermal conductivity of aluminum alloy materials by adding tin-titanium carbide MAX phase materials. When aluminum alloy exterior windows are made, the heat exchange and transfer between the outside and the interior can be effectively reduced, thereby meeting the thermal conductivity requirements of exterior windows for near-zero energy buildings.
[0023] 2. The present invention reduces the effect of reduced mechanical properties caused by the introduction of tin into the alloy material by adding 312 phase carbide aluminum titanium MAX phase material, so that the prepared aluminum alloy material not only has a lower thermal conductivity, but also has good mechanical properties, which can not only meet the thermal conductivity requirements of exterior windows for near-zero energy buildings, but also meet the safety requirements of exterior window components.
[0024] 3. The raw materials of the present invention are sufficient in China and are of suitable price, so that there is no high cost restriction for large-scale production; at the same time, the preparation method is simple and the overall production cost is not high, which is conducive to large-scale industrial production. DETAILED DESCRIPTION
[0025] Example 1
[0026] Weigh the specific raw materials according to Table 1. The preparation steps are as follows:
[0027] (1) placing aluminum titanium carbide MAX phase material and aluminum powder in a ball mill, placing a steel ball with a diameter of 6 mm at a ball-to-material ratio of 10:1, evacuating and filling with argon gas with a purity of ≥ 99.0%, and then ball milling at a speed of 400 r / min for 12 h, then adding tin titanium carbide MAX phase material, and continuing to ball mill at a speed of 400 r / min for 12 h to obtain a mixed powder containing MAX phase material;
[0028] (2) placing an aluminum-manganese master alloy in a ball mill, adding a steel ball with a diameter of 8 mm at a ball-to-material ratio of 15:1, and ball milling at a speed of 500 r / min for 5 h, and then adding an aluminum-cobalt master alloy, an aluminum-chromium master alloy, an aluminum-magnesium master alloy, and an aluminum-nickel master alloy in order, the former master alloy being ball milled before the latter master alloy is added, and when the latter master alloy is added, steel balls are added at a ball-to-material ratio of 15:1 to obtain a master alloy powder;
[0029] (3) The mixed powder containing the MAX phase material obtained in step (1) and the master alloy powder obtained in step (2) were stirred and mixed at 500 rpm for 25 min, then poured into a hot pressing sintering mold cavity coated with boron nitride, and cold pressed at a pressure of 100 MPa for 2 h;
[0030] (4) In an atmosphere of argon with a purity of ≥99.0%, the temperature is increased to 980°C at a heating rate of 10°C / min, kept at that temperature for 140 minutes and then furnace cooled. When the temperature is increased to 700°C, the pressure is increased to 50 MPa at 900°C, and the pressure is maintained until the furnace is cooled.
[0031] Example 2
[0032] Weigh the specific raw materials according to Table 1. The preparation steps are as follows:
[0033] (1) placing aluminum titanium carbide MAX phase material and aluminum powder in a ball mill, placing a steel ball with a diameter of 8 mm at a ball-to-material ratio of 10:1, evacuating and filling with argon gas with a purity of ≥ 99.0%, and then ball milling at a speed of 500 r / min for 10 h, then adding tin titanium carbide MAX phase material, and continuing to ball mill at a speed of 500 r / min for 10 h to obtain a mixed powder containing MAX phase material;
[0034] (2) placing an aluminum-manganese master alloy in a ball mill, adding a steel ball with a diameter of 10 mm at a ball-to-material ratio of 15:1, and ball milling at a speed of 500 r / min for 5 h, and then adding an aluminum-cobalt master alloy, an aluminum-chromium master alloy, an aluminum-magnesium master alloy, and an aluminum-nickel master alloy in order, the former master alloy being ball milled before the latter master alloy is added, and when the latter master alloy is added, steel balls are added at a ball-to-material ratio of 15:1 to obtain a master alloy powder;
[0035] (3) The mixed powder containing the MAX phase material obtained in step (1) and the master alloy powder obtained in step (2) were stirred and mixed at 600 rpm for 20 min, then poured into a hot pressing sintering mold cavity coated with boron nitride, and cold pressed at a pressure of 200 MPa for 1 h;
[0036] (4) In an atmosphere of argon with a purity of ≥99.0%, the temperature is raised to 990°C at a heating rate of 10°C / min, kept at that temperature for 120 minutes and then furnace cooled. When the temperature is raised to 750°C, the pressure is increased to 60 MPa at 900°C, and the pressure is maintained until the furnace is cooled.
[0037] Example 3
[0038] Weigh the specific raw materials according to Table 1. The preparation steps are as follows:
[0039] (1) placing aluminum titanium carbide MAX phase material and aluminum powder in a ball mill, placing a steel ball with a diameter of 8 mm at a ball-to-material ratio of 10:1, evacuating and filling with argon gas with a purity of ≥ 99.0%, and then ball milling at a speed of 500 r / min for 12 h, then adding tin titanium carbide MAX phase material, and continuing to ball mill at a speed of 500 r / min for 12 h to obtain a mixed powder containing MAX phase material;
[0040] (2) placing an aluminum-manganese master alloy in a ball mill, adding a steel ball with a diameter of 10 mm at a ball-to-material ratio of 15:1, and ball milling at a speed of 500 r / min for 6 h, and then adding an aluminum-cobalt master alloy, an aluminum-chromium master alloy, an aluminum-magnesium master alloy, and an aluminum-nickel master alloy in order, the former master alloy being ball milled before the latter master alloy is added, and when the latter master alloy is added, steel balls are added at a ball-to-material ratio of 15:1 to obtain a master alloy powder;
[0041] (3) The mixed powder containing the MAX phase material obtained in step (1) and the master alloy powder obtained in step (2) were stirred and mixed at 600 rpm for 25 min, then poured into a hot pressing sintering mold cavity coated with boron nitride, and cold pressed at a pressure of 200 MPa for 2 h;
[0042] (4) In an atmosphere of argon with a purity of ≥99.0%, the temperature is raised to 990°C at a heating rate of 10°C / min, kept at that temperature for 140 minutes and then furnace cooled. When the temperature is raised to 750°C, the pressure is increased to 60 MPa at 900°C, and the pressure is maintained until the furnace is cooled.
[0043] Comparative Example 1
[0044] Specific raw materials were weighed according to Table 1. Unlike Example 3, no aluminum titanium carbide MAX phase material was added. The remaining preparation steps were as follows:
[0045] (1) Putting tin titanium carbide MAX phase material and aluminum powder into a ball mill, adding a steel ball with a diameter of 8 mm at a ball-to-material ratio of 10:1, evacuating and filling with argon gas with a purity of ≥ 99.0%, and then ball milling at a speed of 500 r / min for 12 h to obtain a mixed powder containing MAX phase material;
[0046] (2) placing an aluminum-manganese master alloy in a ball mill, adding a steel ball with a diameter of 10 mm at a ball-to-material ratio of 15:1, and ball milling at a speed of 500 r / min for 6 h, and then adding an aluminum-cobalt master alloy, an aluminum-chromium master alloy, an aluminum-magnesium master alloy, and an aluminum-nickel master alloy in order, the former master alloy being ball milled before the latter master alloy is added, and when the latter master alloy is added, steel balls are added at a ball-to-material ratio of 15:1 to obtain a master alloy powder;
[0047] (3) The mixed powder containing the MAX phase material obtained in step (1) and the master alloy powder obtained in step (2) were stirred and mixed at 600 rpm for 25 min, then poured into a hot pressing sintering mold cavity coated with boron nitride, and cold pressed at a pressure of 200 MPa for 2 h;
[0048] (4) In an atmosphere of argon with a purity of ≥99.0%, the temperature is raised to 990°C at a heating rate of 10°C / min, kept at that temperature for 140 minutes and then furnace cooled. When the temperature is raised to 750°C, the pressure is increased to 60 MPa at 900°C, and the pressure is maintained until the furnace is cooled.
[0049] Comparative Example 2
[0050] Specific raw materials were weighed according to Table 1. Unlike Example 3, no tin-titanium carbide MAX phase material was added. The preparation steps were as follows:
[0051] (1) placing aluminum titanium carbide MAX phase material and aluminum powder in a ball mill, placing a steel ball with a diameter of 8 mm at a ball-to-material ratio of 10:1, evacuating the jar and filling it with argon gas with a purity of ≥ 99.0%, and then ball milling at a speed of 500 r / min for 12 h to obtain a mixed powder containing the MAX phase material;
[0052] (2) placing an aluminum-manganese master alloy in a ball mill, adding a steel ball with a diameter of 10 mm at a ball-to-material ratio of 15:1, and ball milling at a speed of 500 r / min for 6 h, and then adding an aluminum-cobalt master alloy, an aluminum-chromium master alloy, an aluminum-magnesium master alloy, and an aluminum-nickel master alloy in order, the former master alloy being ball milled before the latter master alloy is added, and when the latter master alloy is added, steel balls are added at a ball-to-material ratio of 15:1 to obtain a master alloy powder;
[0053] (3) The mixed powder containing the MAX phase material obtained in step (1) and the master alloy powder obtained in step (2) were stirred and mixed at 600 rpm for 25 min, then poured into a hot pressing sintering mold cavity coated with boron nitride, and cold pressed at a pressure of 200 MPa for 2 h;
[0054] (4) In an atmosphere of argon with a purity of ≥99.0%, the temperature is raised to 990°C at a heating rate of 10°C / min, kept at that temperature for 140 minutes and then furnace cooled. When the temperature is raised to 750°C, the pressure is increased to 60 MPa at 900°C, and the pressure is maintained until the furnace is cooled.
[0055] Comparative Example 3
[0056] The specific raw materials were weighed according to Table 1. The difference from Example 3 is that the aluminum titanium carbide MAX phase material is Ti 2 AlC, the preparation steps are as follows:
[0057] (1) placing aluminum titanium carbide MAX phase material and aluminum powder in a ball mill, placing a steel ball with a diameter of 8 mm at a ball-to-material ratio of 10:1, evacuating and filling with argon gas with a purity of ≥ 99.0%, and then ball milling at a speed of 500 r / min for 12 h, then adding tin titanium carbide MAX phase material, and continuing to ball mill at a speed of 500 r / min for 12 h to obtain a mixed powder containing MAX phase material;
[0058] (2) placing an aluminum-manganese master alloy in a ball mill, adding a steel ball with a diameter of 10 mm at a ball-to-material ratio of 15:1, and ball milling at a speed of 500 r / min for 6 h, and then adding an aluminum-cobalt master alloy, an aluminum-chromium master alloy, an aluminum-magnesium master alloy, and an aluminum-nickel master alloy in order, the former master alloy being ball milled before the latter master alloy is added, and when the latter master alloy is added, steel balls are added at a ball-to-material ratio of 15:1 to obtain a master alloy powder;
[0059] (3) The mixed powder containing the MAX phase material obtained in step (1) and the master alloy powder obtained in step (2) were stirred and mixed at 600 rpm for 25 min, then poured into a hot pressing sintering mold cavity coated with boron nitride, and cold pressed at a pressure of 200 MPa for 2 h;
[0060] (4) In an atmosphere of argon with a purity of ≥99.0%, the temperature is raised to 990°C at a heating rate of 10°C / min, kept at that temperature for 140 minutes and then furnace cooled. When the temperature is raised to 750°C, the pressure is increased to 60 MPa at 900°C, and the pressure is maintained until the furnace is cooled.
[0061] Comparative Example 4
[0062] The specific raw materials were weighed according to Table 1. The difference from Example 3 is that the aluminum titanium carbide MAX phase material is Ti 4 AlC 3 The remaining preparation steps are as follows:
[0063] (1) placing aluminum titanium carbide MAX phase material and aluminum powder in a ball mill, placing a steel ball with a diameter of 8 mm at a ball-to-material ratio of 10:1, evacuating and filling with argon gas with a purity of ≥ 99.0%, and then ball milling at a speed of 500 r / min for 12 h, then adding tin titanium carbide MAX phase material, and continuing to ball mill at a speed of 500 r / min for 12 h to obtain a mixed powder containing MAX phase material;
[0064] (2) placing an aluminum-manganese master alloy in a ball mill, adding a steel ball with a diameter of 10 mm at a ball-to-material ratio of 15:1, and ball milling at a speed of 500 r / min for 6 h, and then adding an aluminum-cobalt master alloy, an aluminum-chromium master alloy, an aluminum-magnesium master alloy, and an aluminum-nickel master alloy in order, the former master alloy being ball milled before the latter master alloy is added, and when the latter master alloy is added, steel balls are added at a ball-to-material ratio of 15:1 to obtain a master alloy powder;
[0065] (3) The mixed powder containing the MAX phase material obtained in step (1) and the master alloy powder obtained in step (2) were stirred and mixed at 600 rpm for 25 min, then poured into a hot pressing sintering mold cavity coated with boron nitride, and cold pressed at a pressure of 200 MPa for 2 h;
[0066] (4) In an atmosphere of argon with a purity of ≥99.0%, the temperature is raised to 990°C at a heating rate of 10°C / min, kept at that temperature for 140 minutes and then furnace cooled. When the temperature is raised to 750°C, the pressure is increased to 60 MPa at 900°C, and the pressure is maintained until the furnace is cooled.
[0067] Comparative Example 5
[0068] The specific raw materials were weighed according to Table 1. The difference from Example 3 was that aluminum titanium carbide was not added, silicon titanium carbide was added, and aluminum titanium carbide was not added. The remaining preparation steps were as follows:
[0069] (1) Putting silicon carbide titanium MAX phase material and aluminum powder into a ball mill, adding a steel ball with a diameter of 8 mm at a ball-to-material ratio of 10:1, evacuating and filling with argon gas with a purity of ≥99.0%, and then ball milling at a speed of 500 r / min for 12 h, then adding tin carbide titanium MAX phase material, and continuing to ball mill at a speed of 500 r / min for 12 h to obtain a mixed powder containing MAX phase material;
[0070] (2) placing an aluminum-manganese master alloy in a ball mill, adding a steel ball with a diameter of 10 mm at a ball-to-material ratio of 15:1, and ball milling at a speed of 500 r / min for 6 h, and then adding an aluminum-cobalt master alloy, an aluminum-chromium master alloy, an aluminum-magnesium master alloy, and an aluminum-nickel master alloy in order, the former master alloy being ball milled before the latter master alloy is added, and when the latter master alloy is added, steel balls are added at a ball-to-material ratio of 15:1 to obtain a master alloy powder;
[0071] (3) The mixed powder containing the MAX phase material obtained in step (1) and the master alloy powder obtained in step (2) were stirred and mixed at 600 rpm for 25 min, then poured into a hot pressing sintering mold cavity coated with boron nitride, and cold pressed at a pressure of 200 MPa for 2 h;
[0072] (4) In an atmosphere of argon with a purity of ≥99.0%, the temperature is raised to 990°C at a heating rate of 10°C / min, kept at that temperature for 140 minutes and then furnace cooled. When the temperature is raised to 750°C, the pressure is increased to 60 MPa at 900°C, and the pressure is maintained until the furnace is cooled.
[0073] Table 1
[0074]
[0075]
[0076] Example 4 Performance Test
[0077] The aluminum alloys prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were tested for tensile strength, thermal conductivity and other items. The thermal conductivity was measured using a laser thermal conductivity meter to directly measure the horizontal thermal diffusion coefficient, thermal conductivity = thermal diffusion * specific heat * density (W / m*k), and the tensile strength test was carried out in accordance with GB / T228.1-2010. The test results are shown in Table 2.
[0078] Table 2
[0079]
[0080] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.
Claims
1. An aluminum alloy material with low thermal conductivity, characterized in that: The aluminum alloy material is prepared from the following raw materials in percentage by mass: Mn: 0.5-1.0wt%, Co: 0.1-0.4wt%, Mg: 2-4wt%, Cr: 0.1-0.2wt%, Ni: 0.1-0.2wt%, 0.5-1.0wt% of tin-titanium carbide MAX phase material, impurities not exceeding 0.1wt%, and the balance being aluminum.
2. The aluminum alloy material according to claim 1, characterized in that: The source of the aluminum is aluminum powder, and the sources of manganese, magnesium, chromium, cobalt and nickel are intermediate alloys containing aluminum.
3. The aluminum alloy material according to claim 1, characterized in that: The tin titanium carbide MAX phase material includes one of a 312 phase tin titanium carbide MAX phase material and a 211 phase tin titanium carbide MAX phase material, or a combination of both.
4. The aluminum alloy material according to claim 2, characterized in that: The titanium tin carbide MAX phase material is a 211 phase titanium tin carbide MAX phase material, and the 211 phase titanium tin carbide MAX phase material is Ti2SnC.
5. The aluminum alloy material according to claim 4, characterized in that: The aluminum alloy material also includes 2.0-3.0 wt % of aluminum-titanium carbide MAX phase material.
6. The aluminum alloy material according to claim 5, characterized in that: The aluminum titanium carbide MAX phase material includes one or a combination of two or more of 312 phase aluminum titanium carbide MAX phase material, 211 phase aluminum titanium carbide MAX phase material, and 413 phase aluminum titanium carbide MAX phase material.
7. The aluminum alloy material according to claim 6, characterized in that: The aluminum titanium carbide MAX phase material is a 312 phase aluminum titanium carbide MAX phase material, and the 312 phase aluminum titanium carbide MAX phase material is Ti3AlC2.
8. The aluminum alloy material according to claim 7, characterized in that: The aluminum alloy material is prepared from the following raw materials in percentage by mass: Mn: 1.0wt%, Co: 0.4wt%, Mg: 4wt%, Cr: 0.2wt%, Ni: 0.2wt%, 1.0wt% of tin-titanium carbide MAX phase material, 3.0wt% of aluminum-titanium carbide MAX phase material, no more than 0.1wt% of impurities, and the balance is aluminum.
9. A method for preparing an aluminum alloy material with low thermal conductivity according to any one of claims 5 to 8, characterized in that: The preparation method comprises the following steps: (1) placing aluminum titanium carbide MAX phase material and aluminum powder in a ball mill, placing a steel ball with a diameter of 6 to 8 mm at a ball-to-material ratio of 10:1, evacuating and filling with argon gas with a purity of ≥99.0%, and then ball milling at a speed of 400 to 500 r / min for 10 to 12 hours, then adding tin titanium carbide MAX phase material, and continuing to ball mill at a speed of 400 to 500 r / min for 10 to 12 hours to obtain a mixed powder containing MAX phase material; (2) placing an aluminum-manganese master alloy in a ball mill, adding steel balls with a diameter of 8 to 10 mm at a ball-to-material ratio of 15:1, and ball milling at a speed of 400 to 500 r / min for 5 to 6 hours, and then adding an aluminum-cobalt master alloy, an aluminum-chromium master alloy, an aluminum-magnesium master alloy, and an aluminum-nickel master alloy in order, the former master alloy being ball milled before the latter master alloy is added, and when the latter master alloy is added, steel balls are added at a ball-to-material ratio of 15:1 to obtain a master alloy powder; (3) The mixed powder containing the MAX phase material obtained in step (1) and the master alloy powder obtained in step (2) are stirred and mixed at 500-600 rpm for 20-25 min, then poured into a hot pressing sintering mold cavity coated with boron nitride, and cold pressed at a pressure of 100-200 MPa for 1-2 h; (4) In an atmosphere of argon gas with a purity of ≥99.0%, the temperature is raised to 980-990°C at a heating rate of 10°C / min, kept at that temperature for 120-140min and then furnace cooled, wherein pressurization is started when the temperature is raised to 700-750°C, and the pressure is increased to 50-60MPa when the temperature reaches 900°C, and then the pressure is maintained until the furnace is cooled.
Citation Information
Patent Citations
Low-heat-conduction and high-toughness aluminum-manganese-cobalt-series die-cast aluminum alloy and processing technology thereof
CN110592442A
Wear-proof aluminum alloy
CN103526085A
Energy-saving aluminum alloy with low heat conduction and high property
CN104674069A